Fluoroscopic-Guided Removal of Jejunal Sharp Foreign Body: An Alternative Approach to Surgery - Abdulrahman Qatomah; Simon McQueen; Wafa Qatomah; Aishah Qatomah; Ali Bessissow (Case Reports in Gastrointestinal Medicine)
Introduction. Foreign body (FB) ingestion represents a frequently encountered scenario in clinical practice. Most ingested FBs typically pass spontaneously, requiring no intervention. Endoscopic removal stands out as the least invasive method, with only a minimal 1% needing surgical intervention. Case Presentation. We present a case of a 30-year-old male who ingested multiple FBs located in the stomach and small bowel. While successful removal of the stomach FB was achieved through endoscopy, the second FB in the small bowel proved challenging due to perforation concerns and limited expertise. Given a history of prior surgical intervention resulting in a large incisional hernia, surgical removal was discouraged. Consequently, a collaborative decision involving surgeon and interventional radiologist (IR) led to the adoption of a fluoroscopic-guided removal approach facilitated by IR techniques. Conclusion. This case highlights the potential for a less invasive alternative in situations where both endoscopic and surgical interventions are deemed not feasible.